(untitled) (Research, Society and Development, 2021)
The records of products with a geographical indication (GI) are produced in regions that have differences, such as the place and form of production, soil, climate and harvest. This work aimed to delimit the geographical area of GI of Brazilian Southern Plateau (BSP) of honeydew honey bracatinga production through the superposition of phytogeographic, climatic, geological, physiographic and productive criteria. The geographical delimitation of the area was carried out, based on the crossing of maps (political, orthobasins, climate, land cover and use), digital terrain model, and the location of honey producers. The structuring of GI the PSB for bracatinga honeydew honey seeks, in addition to the GI registration, the effective participation of actors in the production chain, in decision-making, in the feasibility of territorial public policies and in the construction of collective agreements. The geographic delimitation made it possible to define the production area that allows obtaining a product of specific qualities. The area of geographic delimitation of the GI honeydew honey bracatinga from the PSB to Santa Catarina is 43,339.5 km2, corresponding to 45.3% of the territory; in Paraná the area of the GI is 8,500.6 km2, corresponding to 8.9% of the territory; and in Rio Grande do Sul, it’s 7,147.0 km2, approximately 7.5% of the territory. More studies must be carried out in the PSB region aiming at the influence of the geographical environment on honeydew honey bracatinga, as well as on the qualitative properties of this honey to demonstrate that this product has unique characteristics.